IMPLEMENTASI KONSEP BANK EMAS PADA PT PEGADAIAN (STUDI KASUS: TRANSFORMASI DARI GADAI KE BANK EMAS) - Rachmad Risqy Kurniawan (Al-Hisbah Jurnal Ekonomi Syariah, 2025)
This research is motivated by the difference between the ideal function of gold banks as a place to store and invest in gold and the practice of PT Pegadaian which makes gold as the main guarantee of credit loan products. This study aims to analyze the implementation of the gold bank concept in PT Pegadaian as a case study. The research method used is descriptive qualitative with a juridical normative approach, which examines the conformity between the legal basis and the implementation of Bullion Bank practices at PT Pegadaian. This research will examine the operational aspects of gold services at Pegadaian and review the related legal basis. The results of the research indicate that the implementation of the Bullion Bank concept at PT Pegadaian is not fully aligned with the ideal function of a Bullion Bank as a storage and investment institution, nor with the role of PT Pegadaian as a credit provider with gold pawn collateral. The conclusion of this research is that Pegadaian's transformation into a Bullion Bank, supported by POJK No. 17 of 2024, expands its services from gold pawn to gold savings, gold installments, and gold trading, while also presenting challenges related to reserve management, the risk of unproductive asset accumulation, gold price volatility, and the potential for a bubble economy.